A quantitative LC–MS method to determine surface contamination of antineoplastic drugs by wipe sampling. Issue 1 (2nd January 2022) - Kåredal, Monica; Jönsson, Rebecca; Wetterling, Maria; Björk, Birgitta; Hedmer, Maria
Abstract: The main objective was to develop a wipe sampling test to measure surface contamination of the most frequently used antineoplastic drugs (ADs) in Swedish healthcare and, furthermore, to develop an analysis method sensitive enough to assess low levels of contamination. Two wipe sampling tests with separate sample processing methods assessing (i) cyclophosphamide (CP), ifosfamide (IF), 5-fluorouracil (5-FU), etoposide (ETO), gemcitabine (GEM) and cytarabine (CYT) (Wipe Test 1); and (ii) GEM, CYT and methotrexate (MTX) (Wipe Test 2), respectively, were developed by optimization of absorption and extraction efficiencies using different wipe tissue materials, tissue wetting solution, and extraction solvents. A fast liquid chromatography tandem mass spectrometry method was developed for simultaneous detection of the studied ADs. The limit of quantification for the method was between 0.04 to 2.4 ng/wipe sample (0.10 to 6.1 pg/cm 2 for an area of 400 cm 2 ) and at 50 ng/sample the within-day precision was between 1.3 and 15%, and the accuracy between 102 and 127%. Wipe Test 1 was applied in an assessment of cleaning efficiency of five different cleaning solutions (formic acid, water, sodium hydroxide, ethanol, and sodium dodecyl sulfate (SDS) for removal of ADs from surfaces made of stainless steel or plastic. For CP, IF, 5-FU, GEM, and CYT 92% of the AD were removed regardless of surface and cleaning solution. In conclusion, a user-friendly assessment method to measure low levels of seven ADs in the work environment was developed and validated. Assessment of the decontamination efficiency of cleaning solutions concerning removal of ADs from stainless steel showed that efficiencies differed depending on the AD with water being the least effective cleaning agent. The results suggests that a combination of different cleaning agents including detergent and a solution with an organic component would be optimal to efficiently remove the measured ADs from surfaces in the workplace.